Secondary school music education : a case study in adapting to ICT resource limitations - Crawford, Renée (Australasian Journal of Educational Technology, 2009)
This article explores the current availability and use of information communication and technology (ICT) for music education purposes, and music technology resources and facilities, in Victorian government secondary schools. Survey data is presented providing a snapshot of the status of computer and technology resources in government secondary schools in several Metropolitan Regions. Discussion is focused on a case study into one particular secondary school and the perceptions of one music teacher and her students regarding class music and ICT. While preferential treatment for resources, particularly access to ICT, was accorded to some disciplines, arts subjects such as music were frequently excluded. Results indicated that reforming music education to reflect contemporary music practice will not only engage student interest, but also assist in raising the status of music in the school curriculum by demonstrating its relevancy. An effective use of ICT and music technology can assist in emulating real life or authentic learning contexts to achieve this pedagogical change. However, a major challenge illustrated in this case study was the paucity of resources, a concern shared by many music educators. Nevertheless, the music teacher in this case study used the minimal resources at her disposal effectively, providing an exemplar of adapting to ICT resource limitations. [Author abstract]